Assessment of Water Supply Sources in Tundia Area, Dilling Locality, South Kordofan State, Sudan - Ali, Hamid Omer; Mustafa, Khalid (World Bank, Washington, DC, 2013)
Tundia, like most areas in South Kordofan was seriously affected by the North-South war, with infrastructure and basic services, particularly water points, left in poor conditions. The increasing number of returnees also exerts additional pressure on the limited water supply points, causing several inter and intra-group conflicts, particularly during summertime. It is envisaged that access to water through improved/rehabilitated and/or construction of additional/new water sources can help reducing tensions between water users, especially in Tundia area. Past water interventions endeavored by the community, NGOs and government, lacked proper planning, real technical input and therefore did not bring long-term sustainable solutions. Notwithstanding other problems and development challenges facing the area, the 5 year plan (2007 - 2011) for development of the area, devised by the Tundia Development and Management Committee has put emphasis on development of water supply sources. The overall objective of this water needs assessment is to contribute to alleviate the water problem, thus improving the socioeconomic conditions and mitigating water-related conflict in Tundia area. To achieve this objective a baseline survey study (supported by the World Bank, April, 2010) was conducted, focusing on a water needs assessment and highlighting the main problems that the population faces in the area. Subsequently, water development options have been suggested.